Evaluation of a Telehealth ABA Program for Caregivers of Children with ASD. Issue 2 (March 2023) - Gerow, Stephanie; Kirkpatrick, Marie; McGinnis, Kristina; Sulak, Tracey N.; Davis, Tonya N.; Fritz, Stephanie
Children with autism spectrum disorder (ASD) often experience skill deficits that can negatively affect long-term outcomes. Interventions based on applied behavior analysis (ABA) yield improvements in targeted skills. However, families often have difficulty accessing ABA services. The purpose of this study was to evaluate the efficacy of a caregiver coaching program delivered via telehealth. Thirty children with ASD and their caregivers (e.g., parents, grandparents) participated in all phases of the study. The program consisted of therapists providing coaching in English or Spanish to caregivers of children with ASD via synchronous video call telehealth visits, typically provided one to two times per week. Caregivers received coaching in interventions (e.g., functional communication training, discrete trial teaching, total task chaining, and naturalistic teaching) to address individualized goals. We collected data on caregiver treatment fidelity and child outcomes (i.e., Vineland-3, observation, and analysis of time series data). Caregivers implemented intervention procedures with 95% accuracy on average. The single-case effect sizes calculated based on the time series baseline and intervention data yielded medium, large, or very large improvements for 85% of goals addressed. Results indicated that the children improved on appropriate engagement (measured via observation), but there was no statistically significant improvement for the remaining pre-post measures. These results, along with the results of previous studies, provide preliminary support for the use of telehealth to provide ABA services. However, there is a need for additional research evaluating the efficacy of these types of programs.